Effects of aerobic exercise on psychosocial traits among people living with HIV/AIDS in Nekemte, Ethiopia - Soumitra Mondal; Girma Tilahun; Dhamodharan Mathivanan; Mohamud Abdulkedar (Turkish Journal of Kinesiology, 2018)
In the recent decades, the positive psycho-social considered as an ability of human beings which are provided appropriate studies in well-being and happiness domains. In this way, the purpose of this research was to identify the effect of twelve weeks aerobic exercise on psychosocial trait among people living with HIV/AIDS. This study was a randomized clinical controlled trial. The Study Population was from Nekemte city of people living with HIV/AIDS (PLWHIV) under antiretroviral therapy (ART). Of PLWHIV under ART two hundred fifty (n= 250) were volunteered and willing to participate. After inclusive and exclusive criteria applied 58 subjects were selected by simple lottery method, strata and randomly assigned in experimental and control groups. World Health Organization quality of life assessment instrument (the WHOQOL) (WHOQOL-brief 1994b) psychosocial questioner was administrated to collect the pre test and after the intervention post test data was collected with same questioner. Experimental group were participated in aerobic exercise programmed for 12 weeks. Control group were encouraged to attend ART and advised usual day to day activity. The collected data were analyzed by paired t-test and independent t-test by using SPSS version 20. The level of significance for all analyses was set at P < 0.05. However, after 12-weeks psychosocial trait had shown significant change (P=0.00) observed in exercise group where as control group insignificant (p=81) and which is an effective complementary therapy to improved psychosocial trait in PLWHA. It was concluded  that the three-month, supervised, and moderate aerobic exercise program, performed three times a week, can improve the psychosocial traits. Aerobic exercise has a positive effect on psychosocial trait in people living with HIV/AIDS when it combines with ART rather than ART alone.